AKHLAK PEMIMPIN SEBAGAI PILAR PERILAKU ORGANISASI DI LEMBAGA PENDIDIKAN ISLAM: - Pryditzia Presdiranti; Ali Nasith (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to examine and analyze the role of leader morals as the main pillar in shaping organizational behavior in Islamic educational institutions. The research uses a qualitative approach with a library research method, through reviewing various relevant literature sources, such as books, scientific articles, journals, and academic documents that discuss Islamic leadership and organizational behavior. Data analysis was conducted by reviewing, interpreting, and synthesizing relevant theories and findings to obtain a comprehensive understanding of the relationship between leadership morals and organizational behavior. The results showed that leader morals have a significant influence in creating conducive, harmonious, and productive organizational behavior in Islamic educational institutions. Leaders who have good morals, such as honesty (Shiddiq), trustworthiness, fairness, wisdom, and responsibility, are able to become moral and spiritual role models for all members of the organization. This example contributes to building an Islamic work culture, increasing motivation, discipline, cooperation, and loyalty of the institution's citizens. Thus, the character of the leader not only serves as the moral foundation of leadership, but also becomes a strategic foundation in shaping organizational behavior that is effective, professional, and oriented towards the values of worship and mutual benefit.